Implementasi Manajemen Kelas dalam Meningkatkan Disiplin Belajar Peserta Didik Kelas V di MI Ma’arif Rejodadi - Siti Uswatun Hasanah; Khoerunnisa Khoerunnisa; Johar Alimuddin (PT. Intelek Cendikiawan Nusantara, 2025)
Discipline plays a very important role for students in achieving success in the future.Discipline is a key factor in achieving success, especially for learners. Discipline itself refers to a set of educational rules that involve adherence to standards or appropriate behavior and activities. Discipline in schools is established through the role of student management, which creates rules that must be followed by everyone within the institution. Student management refers to all planned and deliberate activities as well as continuous guidance for all students within an educational institution, so they can participate in the teaching and learning process effectively and efficiently.